Macular thickness and retinal nerve fiber thickness analysis in ocular dominance - Cevher,Selim (2018)
Abstract Objective: To compare macular and peripapillary retinal nerve fiber layer thicknesses of dominant eye and non-dominant eye using optical coherence tomography (OCT). Methods: 104 eyes of 52 healthy young adults were included. Ophthalmological examinations; including measuring refraction, best corrected visual acuity, intraocular pressure (IOP) measurement, slit-lamb biomicroscopy, dilated fundus examination, measuring of central macular thickness (CMT), and peripapillary retinal nerve fiber layer (PRNFL) thickness were performed on each subject. Hole-in-the-card test was used to detect the ocular dominance. Results: There were 25 females (48%) and 27 males (52%) in the study. Eight participants had left eye dominance (15%), forty-four participants had right eye dominance (85%). Mean CMT was 192.5µm in dominant group and 191.9 µm in non-dominant group. There was no statistically significant difference between dominant eye group and non-dominant eye group in either macular thickness or peripapillary retinal nerve fiber layer thickness. Conclusions: No difference between macular and peripapillary retinal nerve fiber layer thicknesses were detected in dominant and non-dominant groups. Further evaluation is needed.